(E)-1-(3-Hydroxyphenyl)-3-[4-(tetradecyloxy) phenyl]prop-2-en-1-one - Siti Muhaini, Haris Fadzillah; Zainab, Ngaini; Hasnain, Hussain; Ibrahim, Abdul Razak; Safra Izuani, Jama Asik (International Union of Crystallography, 2012)
In the title compound, C29H40O3, the enone moiety adopts an s-cis conformation. The dihedral angle between the benzene rings is 4.33 (5)° The least-squares mean line through the tetradecyl side chain forms a dihedral angle of 83.99 (7)° with the normal to the attached benzene ring. In the crystal, O—H⋯O and C—H⋯O hydrogen bonds involving the keto and the hydroxy O atoms form ribbons along [-41-1]. The crystal structure also features C—H⋯π interactions.